Concomitant generation of hydrogen during carbon dioxide storage in ultramafic massifs- state of the art with implications to decarbonization strategies - Mahmoud Leila; Randy Hazlett; Paul Mathews George; Isabelle Moretti; Zhaksylyk Kabashev; Milovan Fustic (Carbon Capture Science & Technology)
Key strategies to mitigate the detrimental effects of climate change include a rapid transition to green, zero-carbon energy sources coupled with geological storage of CO₂. Mineral trapping of CO₂ recently emerged as one of the most efficient and lowest-risk approaches for long-term CO₂ sequestration. Given the high reactivity of ultramafic lithologies with CO₂, their potential for large-scale mineralization warrants further investigation. In addition to their capacity for CO₂ sequestration, ultramafic massifs are recognized as a potential source of natural hydrogen (H₂) through serpentinization. This dual functionality—CO₂ mineralization and H₂ generation—positions ultramafic lithologies as critical components in the emerging hydrogen economy and decarbonization strategies.This article provides a comprehensive review of the current understanding of the processes governing natural hydrogen (H₂) generation and carbon dioxide (CO₂) mineralization across various ultramafic lithotypes. Although these processes can occur concurrently, the degree of mineral dissolution, oxidation, and subsequent precipitation exhibits substantial variability depending on the lithology. Moreover, the optimal temperature ranges for H₂ generation and CO₂ mineralization differ, further influencing their coupling potential. A viable window for dual functionality appears to involve oxidation–reduction with CO₂-saturated water, which liberates Mg2+ and Fe2+. Subsequently, Mg2+ reacts with excessive CO₂ to precipitate carbonate minerals, while Fe2+ is oxidized to produce H₂. Laboratory experiments demonstrate that specific ultramafic lithotypes enriched in magnesium-bearing mineral phases (e.g. brucite, forsterite, serpentine) are favorable for CO₂ mineralization. Additionally, incorporation of Fe2+ within these mineral phases during stages of serpentinization would be favorable for H₂ production. Mineralogical alterations induced by serpentinization and carbonation processes are characterized by distinct physical and geochemical signatures. These alterations result in significant variations in magnetic susceptibility, rock density, seismic wave velocity, and volatile content. Such measurable changes provide critical diagnostic tools for developing an integrated exploration framework aimed at identifying favorable zones, or ''sweet spots,'' for CO₂ mineralization and H₂ generation within ultramafic lithologies.